Correlation of angle kappa and angle alpha on visual outcomes in eyes implanted with three types of multifocal intraocular lenses - Robert Edward T. Ang; Zoe Alethinos M. Doroy; Justin Alan A. Yao; Emerson M. Cruz (Scientific Reports)
Abstract To evaluate the correlation between preoperative, postoperative, and change in angle kappa and alpha to visual outcomes following implantation of three multifocal intraocular lenses. This is a retrospective study which included 122 eyes of 61 patients. There were 38 eyes in the Synergy (Johnson & Johnson, USA) group and 42 eyes each from both the Panoptix (Alcon Laboratories, USA) and FineVision (Physiol BVI, Belgium) groups. Visual outcome parameters (uncorrected distance, intermediate, near vision, halo and starburst) and angle kappa and alpha were recorded preoperatively and at three months postoperatively. The preoperative, postoperative and the amount of change in angle kappa and alpha were correlated to visual outcomes and photic phenomena among the three different diffractive trifocal IOLs. There were no significant differences in the preoperative and postoperative magnitude of angle kappa and alpha among the Synergy, Panoptix, and FineVision groups. There was no significant correlation between the preoperative and postoperative magnitude, and change in angle kappa and alpha with the postoperative uncorrected distance, intermediate and near visual acuity, and halo and starburst scores of the three different diffractive IOLs. The frequency of eyes with greater than 0.5 mm angle kappa and alpha values were low. Visual outcomes can be good even in eyes in which the angle kappa and alpha were greater than 0.5 mm. The newer diffractive multifocal IOLs were observed to be more tolerant to low and intermediate levels of angle kappa and alpha.